A Self‐Sacrificing N‐Methyltransferase Is the Precursor of the Fungal Natural Product Omphalotin. Issue 33 (17th July 2017) - Ramm, Sascha; Krawczyk, Bartlomiej; Mühlenweg, Agnes; Poch, Annette; Mösker, Eva; Süssmuth, Roderich D.
Abstract: Research on ribosomally synthesized and posttranslationally modified peptides (RiPPs) has led to an increasing understanding of biosynthetic mechanisms, mostly drawn from bacterial examples. In contrast, reports on RiPPs from fungal producers, apart from the amanitins and phalloidins, are still scarce. The fungal cyclopeptide omphalotin A carries multiple N‐methylations on the peptide backbone, a modification previously known only from nonribosomal peptides. Mining the genome of the omphalotin‐producing fungus for a precursor peptide led to the identification of two biosynthesis genes, one encoding a methyltransferase OphMA that catalyzes the automethylation of its C‐terminus, which is then released and cyclized by the protease OphP. Our findings suggest a novel biosynthesis mechanism for a RiPP in which a modifying enzyme bears its own precursor peptide. Abstract : Keep your tail up : The fungal cyclopeptide omphalotin A carries multiple N ‐methylations on the peptide backbone. Genome mining of the omphalotin‐producing fungus for a precursor peptide identified two biosynthesis genes: a methyltransferase OphMA catalyzes the automethylation of its C‐terminus, which is then released and cyclized by the protease OphP. These findings suggest a novel biosynthesis mechanism in which a modifying enzyme bears its own precursor.